TO THE QUESTION OF PROFIT CATEGORY - Myamlin, V. V. (Science and Transport Progress, 2009)
The economic category “profit” is considered. The discrepancies and inconsistency of the existing financial-andeconomic model of management based only upon the “profitable” paradigm is demonstrated. It is shown how a “profit” affects a discrepancy between the supply of goods and the related solvent demand. It is suggested to build the laws of economics starting not from the private interests of separate social groups but from the universal laws of the Nature. The transition from “profit” maximization to wages/salary maximization is recommended. It is proposed to exclude a category “profit” from the financial-and-economic model of management as an unnecessary and imaginary one that continuously leads the economic system to crisis.